2013
DOI: 10.4172/2157-7633.1000141
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Canine Bone Marrow Derived Mesenchymal Stem Cells and its Conditioned Media in Diabetic Rat Wound Healing

Abstract: Present study was conducted to explore the possibility of treating the diabetic rat wounds by canine bone marrow derived mesenchymal stem cells (BMSCs) and its conditioned media (CM). Canine bone marrow stem cells were isolated ascetically from dog and cultured in vitro. Stem cells conditioned media was collected from third passage cells at 120 hours of culture. Streptozotocin was used for induction of diabetes in rats. Six groups were made for the wound healing therapy in which group I, II and III were non-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 34 publications
4
24
1
Order By: Relevance
“…The different isolation methods could be responsible for the observed differences in collagen type II expression (Guest et al, 2008). Expression of the genes of haematopoetic stem cell markers (CD34 and CD45) was lacking in present study as reported by others (Guest et al, 2008;Gade et al, 2013;Ansari et al, 2013). However, there are reports that showed MSCs expression of the CD34 and CD45 surface markers, with one report showing their dim expression (Tan et al, 2013) and other reported that MSCs have heterogeneous CD34 and CD45 phenotype that changes under in vitro conditions (Kaiser et al, 2007).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…The different isolation methods could be responsible for the observed differences in collagen type II expression (Guest et al, 2008). Expression of the genes of haematopoetic stem cell markers (CD34 and CD45) was lacking in present study as reported by others (Guest et al, 2008;Gade et al, 2013;Ansari et al, 2013). However, there are reports that showed MSCs expression of the CD34 and CD45 surface markers, with one report showing their dim expression (Tan et al, 2013) and other reported that MSCs have heterogeneous CD34 and CD45 phenotype that changes under in vitro conditions (Kaiser et al, 2007).…”
Section: Discussioncontrasting
confidence: 49%
“…Isolation of rMSCs was performed by a standard method reported earlier (Pittenger et al, 1999;Woodbury et al, 2002;Ansari et al, 2013;Udehiya et al, 2013). The rMSCs on the basis of morphology, cell frequency rate and molecular marker profile were similar to the canine, murine, porcine, rodent or human MSCs (Castro-Malaspina et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Topical administration of hCB MSCs, and cWJ, MSCs in the cutaneous wounds of mice (diabetic [Liu et al, ] and normal [Tark et al, ]) and rat [Pratheesh et al, ], respectively have exhibited positive effects on wound healing. Wound healing potential of MSCs have also been investigated in mice, rat, rabbit, canine, and human by different groups (McFarlin et al, ; Wu et al, ; Yoshikawa et al, ; Borena et al, ; Ansari et al, ). MSCs improve cutaneous wound healing by stimulating cellular response to injury and promote regeneration rather than scar formation (Rustad et al, ).…”
mentioning
confidence: 99%
“…Apart from proliferation ability, lineage differentiation potential is another important criterion for characterization of MSCs. MSCs were successfully differentiated in all the three lineages confirming the cell suitability for cartilage and bone‐related injuries (Ansari et al, ). Canine MSCs cultured in bFGF supplemented media get differentiated in neuronal cells (Nakano et al, ).…”
Section: Discussionmentioning
confidence: 69%